Synoptic Conditions at Pressure Different Levels for the Dust Storm of May/ 2022 Over Iraq - Al-khakani, Ebtihal; Hamed, Alyaa Matai (Faculty of Geography, Universitas Gadjah Mada, 2024)
This study examines the severe dust storm from May 12-16/2022,culminating on May 15, with a comprehensive analysis and explanation. The weather maps from the National Oceanic and Atmospheric Administration (NOAA) and the European Centre for Medium-Range Weather Forecasts (ECMWF) weather maps were used to identify systems and patterns that contributed to the storm's activity, continuity, and tracking as well as maps of pressure compounds and wind vectors in levels 1000 and 850 mbar that appear with the dust state for the same days accompanied by tracking patterns in the middle of the turbosphere 500 mbar to give a comprehensive analytical view of climate conditions at each level of pressure and higher systems supportive of their persistence on the surface. The northwesterly winds are the main factor that carries dust over long distances. The eastern desert in Syria, the Empty Quarter in the Kingdom of Saudi Arabia, the desert of western Iran, and the desert region of western Iraq are among the main sources of dust In its atmosphere. Based on weather maps of the surface and upper levels of storm days, the concentration of dust reached very high levels in Iraq's airspace and surrounding countries, including Egypt, Jordan, Lebanon, Palestine, and Syria. The intensity of the dust gradually decreased as the area was affected by wet westerly winds with relatively low temperatures and a relative increase in wind speeds due to the impact of the study area on the atmospheric decline centered around the Turkish island of Cyprus.